FAKTOR DETERMINAN PENGUNGKAPAN SUKARELA OLEH YAYASAN DI INDONESIA - Marfuah Marfuah; Alifia Rachma Diani; Chivalrind G Ayuntari (Media Riset Akuntansi, Auditing & Informasi, 2021)
The purpose of this study was to determine the effect of donations, restricted funds, organizational size, and age of the organization age on the voluntary disclosure of the foundation. All foundations in Indonesia are the population in this study. The sample of this research is foundations in Indonesia that submit financial reports via the internet between 2013-2019 and have complete data. Based on these criteria, 114 financial reports were obtained as the research sample. The results of this study prove that restricted funds and organizational size have a significant positive effect on voluntary disclosure, while the donations and age of the organization have no significant positive effect on voluntary disclosure. The implication of this research is that funders must consider the restricted funds and the size of the organization to assess the prospects of the foundation. In addition, the foundation must increase voluntary disclosure to be more transparent in providing information about its foundation. With transparency, the foundation will more easily get the trust to receive funds that are beneficial to the foundation's survival.